The association between vigour and flexibility with injury and alertness during shift work - Simon Folkard (Chronobiology International, 2024)
Models of shift work and health suggest that individual differences in circadian rhythm characteristics may moderate the relationship between night shift work and injury, but this argument has not been directly tested. In this study, we tested the efficacy of two circadian rhythm characteristics—vigour and flexibility—as moderators of the path between shift work and injury. In addition, we aimed to replicate the association between vigour, flexibility, and alertness by time of day, and the measurement properties of the Circadian Type Inventory. We recruited 401 healthcare workers from Australia and Great Britain. After controlling for confounding variables, the results showed that vigour moderated the association between shift work and injury. Participants with values of vigour at the mean (β = 0.5120, p < 0.0013, 95% CI = [0.2018, 0.8223) and one standard deviation below the mean (β = 0.9048, p < 0.0001, 95% CI = [0.4648, 1.3447] reported significantly more injuries. No moderation was found for flexibility. Significant differences in alertness by time of day were observed in participants with higher levels of vigour compared to lower levels of vigour. No differences in alertness were observed for the flexibility scale. These results indicate that vigour may be a robust indicator of shift work tolerance. We replicated the posited two-factor structure of the Circadian Type Inventory, found the scales to have good reliability, and established for the first time, criterion-related validity for the vigour scale.